2009
DOI: 10.1128/jvi.00327-09
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus Type 1 Gag p24 Alters the Composition of Immunoproteasomes and Affects Antigen Presentation

Abstract: Proteasomes are the major source of proteases responsible for the generation of peptides bound to major histocompatibility complex class I molecules. Antigens, adjuvants, and cytokines can modulate the composition and enzymatic activity of proteasomes and thus alter the epitopes generated. In the present study, we examined the effect of human immunodeficiency virus type 1 (HIV-1) p24 on proteasomes from a dendritic cell line (JAWS II), from a macrophage cell line (C2.3), and from murine primary bone marrow-der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 69 publications
0
21
0
Order By: Relevance
“…The concentration of the isolated proteasomes was determined using the (BCA) (Pierce, Rockford, IL). The composition of the isolated proteasomes was determined by two-dimensional isoelectrophoresis/SDS-PAGE (2-D IEF) followed by Western Blot detection of either the constitutive proteasome subunits or the immunoproteasome subunits (ENZOLifeSciences) [30], [31].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration of the isolated proteasomes was determined using the (BCA) (Pierce, Rockford, IL). The composition of the isolated proteasomes was determined by two-dimensional isoelectrophoresis/SDS-PAGE (2-D IEF) followed by Western Blot detection of either the constitutive proteasome subunits or the immunoproteasome subunits (ENZOLifeSciences) [30], [31].…”
Section: Methodsmentioning
confidence: 99%
“…Based on previously described methods [30], [31] 10 µg of CelTOS were incubated with purified proteasomes (1 µg) or with each of the respective CAT (0.5 µg) for 16 hrs at 37°C unless otherwise stated. To ensure the specificity of proteasomes, epoxomicin was used as an inhibitor (EnzoLifeSciences, Farmingdale, NY).…”
Section: Methodsmentioning
confidence: 99%
“…The concentration of proteasomes was determined using the bicinchoninic acid (BCA) assay. The constitutive and immunoproteasome subunits were identified by two-dimensional (2-D) isoelectrophoresis/SDS-PAGE followed by Western blotting as previously described (59,60). The dried blots were scanned using UMAX VistaScan software.…”
Section: Methodsmentioning
confidence: 99%
“…This results in a more efficient generation and presentation of subdominant CTL epitopes (20). We have previously demonstrated that Gag-p24 downregulates the PA28␤ subunit in murine DC and therefore interferes with PA28␣/␤ cap formation, resulting in a decrease in antigen presentation (60).…”
mentioning
confidence: 99%
See 1 more Smart Citation